Accessory Splenic Artery Causing Massive Gastrointestinal Bleed. Issue 3 (10th March 2021) - Patel, Priyesh; Chadalavada, Pravallika; Singh, Amandeep; Gurajala, Ram Kishore; Achkar, Jean-Paul
ABSTRACT: The presentation of an upper gastrointestinal bleed secondary to an accessory splenic artery is a rare circumstance described only in 2 previous case reports. This report is the first to describe an upper gastrointestinal bleed consequent of a submucosal accessory splenic artery arising from the left phrenic artery, requiring multiple endoscopies and endovascular embolization. Vascular anatomic variants can pose a challenge to treatment, especially when they are unknown. This case adds to the limited number of case reports involving accessory splenic arteries.